2016
DOI: 10.3791/54048
|View full text |Cite
|
Sign up to set email alerts
|

Stem-cell Based Engineered Immunity Against HIV Infection in the Humanized Mouse Model

Abstract: With the rapid development of stem cell-based gene therapies against HIV, there is pressing requirement for an animal model to study the hematopoietic differentiation and immune function of the genetically modified cells. The humanized Bone-marrow/Liver/Thymus (BLT) mouse model allows for full reconstitution of a human immune system in the periphery, which includes T cells, B cells, NK cells and monocytes. The human thymic implant also allows for thymic selection of T cells in autologous thymic tissue. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…To provide a source of naive MHC class I-restricted anti-SL9 CD8 T cells, a fraction of the CD34 + hematopoietic stem cells (HSCs) used in the reconstitution was transduced with a vector encoding an SL9-specific human T cell receptor (TCR). [44][45][46] Analysis of the PBMCs by flow cytometry showed that >60% of the lymphocytes in the BLT mice were of human origin ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide a source of naive MHC class I-restricted anti-SL9 CD8 T cells, a fraction of the CD34 + hematopoietic stem cells (HSCs) used in the reconstitution was transduced with a vector encoding an SL9-specific human T cell receptor (TCR). [44][45][46] Analysis of the PBMCs by flow cytometry showed that >60% of the lymphocytes in the BLT mice were of human origin ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The other half were injected retro-orbitally after transplant. 46 For all humanized mice, the engraftment frequency was determined by staining the blood lymphocytes and splenocytes for human CD45 and found to be 60%-90%, resulting in 0.5-2 Â 10 6 human lymphocytes/mL in the blood and 1-3 Â 10 7 human lymphocytes in the spleen. For the SL9 TCR BLT mice, engraftment of the SL9 TCR-transduced CD34 + cells resulted in the expression of SL9 TCR in 0.1%-1.4% of the human CD8 T cells.…”
Section: Blt Micementioning
confidence: 99%
“…Rhesus macaques inoculated with an AAV vector expressing this antibody were protected from several infectious challenges with SIV and thus functioned like an effective HIV-1 vaccine [97]. The data from these studies and others [98100] suggest that gene therapy with CAR may be a potentially effective therapy for chronic HIV infection.…”
Section: Gene Editing: Ex Vivo Strategymentioning
confidence: 99%
“…[30][31][32] The use of this CD4fCAR has important advantages, in that it has been found to be a safe reagent in multiple long-term clinical trials with over 500 patient years of clinical safety data 33,34 and this is strong evidence that it does not induce cytokine storms that have been an unwanted element with other CAR-based approaches in treating malignancies. 35,36 It is also unlikely to generate escape variants of HIV envelope as the loss of CD4 binding of an escape variant will likely have a dramatic effect on viral fitness.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 99%
“…We and others have done extensive testing of the antiviral function of CD8 + T cells transduced with CD4f CAR, finding that transduced cells are capable of killing HIV-infected cells and suppressing viral replication [30][31][32]34,37 and (unlike the HIV-specific TCR) that this activity is independent of HLA-I molecules. 38 CARs can also function in CD4 + T cells to act as HIV-1-specific helper cells.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 99%